Treatment of psychosis in Parkinson's disease: Missed opportunities to discuss about sudden death. (October 2020) - Scorza, Fulvio A.; de Almeida, Antonio-Carlos G.; Scorza, Carla A.; Fiorini, Ana C.; Rodrigues, Antônio Márcio; Finsterer, Josef
Highlights: Clinical research and adverse events associated with the use of antipsychotics in Parkinson's disease. Unexpected death of a PD patient without any satisfactory cause of death has been shown. Clinical studies suggest that some antipsychotics may be related with cardiovascular adverse events. Routine cardiovascular screening should be repeatedly performed in patients with PD considered to be at higher risk.